2023
DOI: 10.1029/2022jd038222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity Beyond Coalescence on Submicron Aerosol Distributions

Abstract: Bubbles entrained by ocean waves rise to the surface and burst, creating a shower of droplets which contribute to sea spray aerosols. Submicron‐sized droplets, of which an estimated 60%–80% come from a bursting bubble film cap, play a key role in global climate atmospheric processes. However, many aspects of predicting the number and size of submicron drops emitted from a bursting bubble remain unknown. It is well‐documented that higher salinity increases submicron droplet production, which has been attributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Zinke et al 54 relates this to a transition in bubble coalescence with salinity. Recently, Dubitsky et al 55 showed experimental evidence suggesting that salinity affects sub-micron aerosol production by affecting the length scale of the bursting bubble film across different salts, bubble coalescence and bubble generation mechanisms. While the mechanism is not clear we speculate that there could be a link between the potential effect of salt on underwater bubble size distribution, bubble surface lifetime and bubble film thickness and the transfer of polystyrene nanoplastic to air via bubble bursting.…”
Section: Resultsmentioning
confidence: 99%
“…Zinke et al 54 relates this to a transition in bubble coalescence with salinity. Recently, Dubitsky et al 55 showed experimental evidence suggesting that salinity affects sub-micron aerosol production by affecting the length scale of the bursting bubble film across different salts, bubble coalescence and bubble generation mechanisms. While the mechanism is not clear we speculate that there could be a link between the potential effect of salt on underwater bubble size distribution, bubble surface lifetime and bubble film thickness and the transfer of polystyrene nanoplastic to air via bubble bursting.…”
Section: Resultsmentioning
confidence: 99%
“…Data for theoretical models described in the text and used to generate the figures are available at OpenBU: Boston University Libraries (Dubitsky et al., 2024).…”
Section: Data Availability Statementmentioning
confidence: 99%